2014
DOI: 10.1103/physrevlett.112.151101
|View full text |Cite
|
Sign up to set email alerts
|

Instability Windows and Evolution of Rapidly Rotating Neutron Stars

Abstract: We consider an instability of rapidly rotating neutron stars in low-mass x-ray binaries (LMXBs) with respect to excitation of r modes (which are analogous to Earth's Rossby waves controlled by the Coriolis force). We argue that finite temperature effects in the superfluid core of a neutron star lead to a resonance coupling and enhanced damping (and hence stability) of oscillation modes at certain stellar temperatures. Using a simple phenomenological model we demonstrate that neutron stars with high spin freque… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
79
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(83 citation statements)
references
References 72 publications
(176 reference statements)
4
79
0
Order By: Relevance
“…A possible solution to this problem was suggested in our recent paper [33] and is discussed in more detail here. Our key idea consists in that to study evolution of NSs in LMXBs one has to correctly take into account the resonance interaction between the normal oscillation m = 2 r-mode and superfluid inertial modes, which occurs at some fixed values of T ∞ (see Sec.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…A possible solution to this problem was suggested in our recent paper [33] and is discussed in more detail here. Our key idea consists in that to study evolution of NSs in LMXBs one has to correctly take into account the resonance interaction between the normal oscillation m = 2 r-mode and superfluid inertial modes, which occurs at some fixed values of T ∞ (see Sec.…”
Section: Introductionmentioning
confidence: 94%
“…Point B lies on the instability curve at T ∞ = T ∞ eq , and specifies the frequency of point C. Points D and E do not depend on the position of m = 2 r o -mode instability curve. 16 In principle, the magnetic field can limit accretion spin-up before reaching point D [33,87]. 17 It is convenient to use −τ GR II instead of τ Diss II in Eq.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…General equations that describe evolution of a NS affected by r-mode instability were formulated by Lindblom et al (1998) (see also Levin 1999;Ho & Lai 2000;Alford & Schwenzer 2014a;Gusakov et al 2014b) and the typical evolution track is shown by a thick black line in Fig. 1.…”
Section: Minimal R-mode Instability Modelmentioning
confidence: 99%
“…11 by dots with error bars associated with uncertainty in thermal insulating envelope composition; data are taken from Gusakov, Chugunov & Kantor 2014b;Chugunov, Gusakov & Kantor 2017) reveal the inadequacy of the standard model: additional dissipation of r-modes is required to stabilize many observed NSs [i.e., all NSs in the white region of 11(a)]. Chugunov et al (2017) analyze the formation of MSPs via the recycling scenario (Bisnovatyi-Kogan & Komberg 1976;Alpar et al 1982;Bhattacharya & van den Heuvel 1991;Papitto et al 2013) and suggest 'minimal' constraints to the instability windows, which allow them to explain the observations of transiently accreting neutron stars, and the formation of high-frequency MSPs, simultaneously.…”
Section: Upper Limit For Surface Temperature Of Msp 47 Tuc Aa and Conmentioning
confidence: 99%